Jornalismo e a memória social do basquete em Campina: podcast é cesta - Nascimento, Geovanna Teixeira (2023)
Rede Ita is an affiliate of TV Cultura in Campina Grande, Paraíba, and since 2012 dedicates part of its programming to daily coverage and transmission of Basquete Unifacisa games, being the first open TV station in Paraíba to broadcast games consistently modality for the population. The present work aims to understand how Rede Ita (former TV Itararé) contributed to the creation of basketball culture in the city and for this purpose a series with four podcasts entitled "Podcast É Cesta!" recorded in a studio, in person, with seven interviewees. The work was done, firstly, from the search for a theoretical framework on journalism and memory, sports journalism, sports television broadcasts and podcasts elaboration processes. As a result of the present study, we understand how the broadcaster from Campinas contributed to the popularization of basketball in Campina Grande, being an important agent in the construction of basketball culture in the city, through didactic materials about the modality, game broadcasts and special reports. The final product, with the four programs, is available on Youtube and streaming platforms for free: https://linktr.ee/podcastecesta